A qualitative study about cancer outpatients' experiences with selective taste control of bread as a self‐care intervention. Issue 6 (19th June 2021) - Corremans, Marleen; Goossens, Edwig; Adriaenssens, Jef; Mortelmans, Dimitri; Geurden, Bart
Abstract: Aim: Alterations in taste are distressing side effects for cancer patients receiving chemotherapy. The Center for Gastrology (Belgium) developed a self‐care intervention based on taste control. This intervention contains an assessment of the individual taste and food hedonics. It provides recipes based on the individual assessed hedonics profile, so patients can self‐prepare personalized meals. This study aims to describe the experiences of oncologic patients with the home baking of personalized bread. Design: A qualitative, descriptive design with individual semi‐structured interviews was used. Methods: In August 2018, eleven face‐to‐face interviews were conducted until data saturation. Results: The analysis of the interviews revealed five major themes: "Stepping out of your role, " "Having something positive to do, " "gaining insight, " "receiving recognition" and "practical limitations."